Muslim-Christian Coexistence in Southeast Asia: A Comparative Study of the Philippines and Indonesia - Demalon, Bai Honey; Siddiq, Akhmad (Religió Jurnal Studi Agama-agama, 2026)
This article examines how historical power relations and state approaches to religious diversity shape Muslim–Christian coexistence in Southeast Asia. Positioned within scholarship on interfaith relations and peacebuilding, the study argues that colonial legacies, political governance, and institutional arrangements largely determine patterns of coexistence. Using a comparative qualitative approach, the paper analyzes interfaith relations in the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM) and Indonesia through historical contextualization and institutional comparison. In the Southern Philippines, Islam existed as an established political and social order before Spanish and American colonization; however, colonial rule transformed religious identity into a marker of political domination and resistance. As a result, contemporary peacebuilding in BARMM emphasizes political autonomy and structural redress, while interfaith dialogue plays a secondary role. In contrast, Indonesia has developed a model of institutionalized religious pluralism grounded in the Pancasila ideology, constitutional frameworks, and formal interfaith bodies such as the Forum Kerukunan Umat Beragama (FKUB). The findings indicate that durable interfaith coexistence depends on the alignment of historical justice, shared civic ideology, and sustained institutional dialogue.